EROSITA detection rates for tidal disruptions of white dwarfs by intermediate mass black holes. Issue 4 (20th September 2019) - Malyali, A; Rau, A; Nandra, K
ABSTRACT: White dwarf black hole tidal disruption events (herein WTDEs) present an opportunity to probe the quiescent intermediate mass black hole population in the Universe. We run an extensive set of Monte Carlo based simulations to explore SRG/eROSITA's detection sensitivity to WTDEs as a function of black hole mass, redshift, and time offset between event flaring and it first being observed. A novel estimate of WTDE rate densities from globular clusters and dwarf galaxies is also presented. We combine this with estimated detection sensitivities to infer the rate of eROSITA detecting these events. Depending on the estimate of the intrinsic rate of WTDEs, we anticipate that eROSITA may detect three events over its 4 yr all-sky survey. eROSITA will be most sensitive to systems with black hole masses above $10^4\, M_{\odot }$, and is most likely to catch these within 5 d of flaring.